QTc INTERVAL AND INSULIN RESISTANCE IN TYPE 2 DIABETES MELLITUS - Timar, Romulus; Popescu, Simona; Simu, Mihaela; Diaconu, Laura; Timar, Bogdan (European Scientific Journal, ESJ, 2013)
﻿﻿﻿﻿﻿Introduction: Patients with type 2 diabetes mellitus (DM) are at increased risk of dying from cardiovascular diseases. Elevated cardiovascular risk in this population persists even after other conventional cardiovascular risk factors are eliminated or reduced, suggesting that there are other, incompletely understood, mechanisms which are increasing cardiovascular risk in such patients. Ventricular instability, such as that observed in QT abnormalities, may be an important additional mechanism. QT prolongation has been shown to predict cardiac death in type 2 DM. The aims of our study were to evaluate the prevalence of QTc prolongation in patients with type 2 DM and to assess the relationship between insulin resistance, evaluated by HOMA-IR and QTc. We also investigated the relationship between QTc and the duration of DM, HbA1c, plasma lipids, systolic blood pressure (SBP), diastolic blood pressure (DBP) and body mass index (BMI). Materials and method: We enrolled 104 patients with type 2 DM. For each subject, 100 consecutive heart beats were recorded on the resting ECG tracing. QTc was calculated according to Bazett’s formula. Results and discussion: In patients with type 2 DM, the prevalence of a prolonged QTc interval was 34.6%. We found a significant increase, with 64 ms (p= 0.004) in QTc interval for the insulin resistant cohort (mean QTc= 419 ms; n= 92) compared to the sample with normal HOMA IR (mean QTc= 355; n=12). Conclusion: Insulin resistance, estimated by HOMA-IR, was strongly correlated with prolonged QTc. Prolonged QTc identifies type 2 DM patients with an elevated risk of cardiovascular events.